Respuesta :
The answer is f(x) = 2x2 + 3x – 3
f(x) = ax² + bx + c
a - the leading coefficient
c - the constant term
We are looking for a = 2, c = -3
Through the process of elimination:
The first (f(x) = 2x3 – 3) and the third choice (f(x) = –3x3 + 2) have x³ so these are not quadratic function.
In the function: f(x) = –3x2 – 3x + 2
a = -3
c = 2
In the function: f(x) = 2x2 + 3x – 3
a = 2
c = -3
f(x) = ax² + bx + c
a - the leading coefficient
c - the constant term
We are looking for a = 2, c = -3
Through the process of elimination:
The first (f(x) = 2x3 – 3) and the third choice (f(x) = –3x3 + 2) have x³ so these are not quadratic function.
In the function: f(x) = –3x2 – 3x + 2
a = -3
c = 2
In the function: f(x) = 2x2 + 3x – 3
a = 2
c = -3
Answer:
the answer is D
Step-by-step explanation:
just took the test
u r welcome